Giles of Lessines on Starlight and the Colour of the Sky - Nothaft, Carl (My University, 2021)
This article provides the first discussion of the unpublished treatise De crepusculis (“On twilight”), written in the second half of the thirteenth century by the Dominican scholar Giles of Lessines. It is shown that De crepusculis was intended as a critical supplement to a treatise on the height of the atmosphere by Ibn Muʿādh (eleventh century). In this supplement, Giles recapitulates Ibn Muʿādh’s geometrical arguments while furnishing proofs and covering relevant questions not included in the earlier work. One area where Giles greatly expands on his predecessor is in addressing relevant physical questions such as the causes of stellar luminosity. Giles here takes a nuanced view, acknowledging that all celestial bodies emit some form of light. He also provides a unique explanation of the blue colour of the sky, which draws on the extramission postulate used by thirteenth-century writers on optics.
PUBLISHED
Keywords: De crepusculis; Thirteenth century; Science; Manuscript, Book and Print Cultures